Entrepreneurship in policing and criminal contexts - Smith, Robert (Emerald Publishing Limited, 2021)
'Entrepreneurship in Policing and Criminal Contexts' explores the contemporary and under researched themes of 'entrepreneurial policing' and 'entrepreneurialism in criminal justice contexts' which are emerging topics of both theoretical and practical interest in the current rapidly changing criminal justice environment. This volume of 'Contemporary Issues in Entrepreneurship Research 'critically opens up a new area of policing research, innovatively using theories of entrepreneurship, management and leadership, to illuminate a novel aspect of policing. Moreover, it presents a scholarly discussion about concepts and theories underpinning the topic. It is evident from readings that there are numerous crossovers in the literatures of entrepreneurship and policing because innovation, transformation and change are integral facets of both phenomena. This timely contribution spans theories of criminology, entrepreneurship and policing and as such is a seminal work which will engage practitioners, scholars and students of entrepreneurship and policing in thinking differently about how entrepreneurship can help change traditional thinking in relation to policing and criminal contexts.
Includes index.
Keywords: Entrepreneurship -- Social aspects.; Police administration.; Criminology.; Business & Economics -- Entrepreneurship.; Entrepreneurship.; elektronické knihy; electronic books